IMPLEMENTASI ARSIP DIGITAL DALAM UPAYA PELESTARIAN ARSIP FISIK PASCA BENCANA OLEH DINAS ARSIP DAN PERPUSTAKAAN PROVINSI JAWA TENGAH - Rizky Ma'ruf (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2026)
This study examines the implementation of digital archives by the Central Java Provincial Archives and Library Service in an effort to preserve physical archives following a disaster. Archives play a vital role as sources of data and evidence; however, Indonesia is prone to natural disasters that can damage physical archives. The digitization of archives is considered an effective way to protect and preserve archival information. The research methodology employs a literature review approach by examining various relevant sources of literature on the implementation of digital archives. Data were analyzed using descriptive qualitative methods to understand the implementation of digital archives. The results indicate that the Archives and Library Service implements digital archives by converting physical archives into digital formats, thereby reducing the risk of loss or damage caused by disasters. Digitization also facilitates information management and access, although its implementation still faces various challenges such as limitations in human resources, digital facilities and infrastructure, and data security. The study concludes that digital archives are crucial for the preservation of physical archives post-disaster, with a need for improvements in human resources, technological infrastructure, and digital security systems.